AKIBAT HUKUM ANAK YANG LAHIR DARI PERJANJIAN SEWA RAHIM (SURROGACY CONTRACT) - Sawsan Yasmine Ohoiwutun; Hanafi Tanawijaya (Jurnal Hukum Adigama, 2022)
The existence of the practice of renting a womb carried out by the community raises many legal problems, whichmust be responded to by all parties. Indonesia does not yet have specific and specific rules regarding the rentalof the womb. If you want to know the rules and regulations related to the issue of uterine rental, then they arerelated and related to several laws and regulations that apply in Indonesia. For example, what is the legal statusof the child born from the rental of the womb. This study is to determine the legal consequences of children bornfrom a womb rental agreement. This study aims to determine the legal certainty of children born from the resultsof a uterine rental agreement. Legal relationship, namely if the child is born from a woman whose womb isrented who is bound by marriage (has a husband) then the child will be domiciled as the legal child of thewoman. In Islamic law, the practice of renting a uterus is not permitted.